ANALISIS RAGAM GABUNGAN LINTAS LOKASI PEMUPUKAN PADI SAWAH DI KABUPATEN GOWA SULAWESI SELATAN - Herniwatin, Nfn (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2014)
The combined analysis of variance is a method to analyze the interaction between treatments and the environments, conducted in farmers' fields. The combined analysis of variance across locations based on the assessment data of organic and inorganic fertilizer is with the model Yijk = u + Li + Î´ik + Tj + ( LT ) ij + Îµijk conducted in Gowa from April to August 2012. The combined analysis can be applied as a test method of fertilization on farmers land that have different characteristics as to accommodate the influence of the land, treatments, and their interactions. The use of combined analysis of variance reveals the real effect of a single factor of fertilization, land factors, and their interaction, to several yield components, but to the component of growth there was no interaction between the two. It can be seen that the combined application of organic manures with inorganic fertilizers can increase rice production. Interaction between land 1 ( L1 ) with organic fertilizer of 5 t / ha + 200 kg Urea/ha + 300 kg NPK / ha ( T4 ) gave the highest paddy production (8,23 t / ha).